Analisis Pengaruh Layout Kantor Yang Cerdas Untuk Meningkatkan Produktivitas Karyawan : Studi Pada PT. Chunsan Group Indonesia - Kamila Nisa Az-Zahra; Soraya Kautsar (Jurnal Inovasi Manajemen, Kewirausahaan, Bisnis dan Digital, 2024)
Office layout arrangements have an important role in increasing employee effectiveness in a dynamic work environment. This research explores the impact of smart office layout arrangements on increasing employee productivity at PT. Chunsan Group Indonesia. The goal is to provide an in-depth understanding of office layout settings that can increase productivity. The research method involves data collection and in-depth interviews in an office layout setting. The research findings emphasize the importance of applying office layout theory efficiently to increase productivity. The conclusion is that smart office layout settings can play a role in increasing employee productivity and comfort in the company. The recommendation from this research is that organizations, including PT. Chunsan Group Indonesia pays close attention to office layout design to create an optimal work environment. It is hoped that the implications of this research can help organizations design office layouts that support employee productivity and achieve company goals.